Generalized fractional integral inequalities of Hermite-Hadamard-type for a convex function - Han, Jiangfeng; Mohammed, Pshtiwan Othman; Zeng, Huidan (Open mathematics (Warsaw, Poland), 2020)
The primary objective of this research is to establish the generalized fractional integral inequalities of Hermite-Hadamard-type for -convex functions and to explore some new Hermite-Hadamard-type inequalities in a form of Riemann-Liouville fractional integrals as well as classical integrals. It is worth mentioning that our work generalizes and extends the results appeared in the literature.